Ferritic stainless steel and its manufacturing method
By adjusting the chemical composition and process treatment of high-Al-containing ferritic stainless steel, the problem of difficult to balance high-temperature oxidation resistance and toughness in the prior art is solved, and the excellent oxidation performance and good processability of steel under high temperature conditions are achieved.
Patent Information
- Application Number
- JP2023566272
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-12-09
- Filing Date
- 2022-12-01
- Publication Date
- 2025-05-01
- Estimated Expiration
- 2042-12-01
AI Technical Summary
The existing high-Al-containing ferritic stainless steel may lead to deterioration of corrosion resistance and poor processability when increasing the Al and Mo content, especially the difficulty in taking into account high-temperature oxidation resistance and toughness.
By adjusting the chemical composition, limiting the content of Al at 2.0-4.0%, controlling the content of Mo, combining other elements such as Ni, Nb, B and REM, optimizing the microstructure of the steel and improving its high-temperature oxidation performance and toughness. Specific measures include increasing the strain value during the cold rolling process, forming an appropriate amount of Nb carbide, and controlling grain boundary density and carbide distribution through specific heat treatment and cold rolling processes.
It achieves a balance between high-temperature oxidation performance and toughness, improves the overall performance of steel, and makes it have excellent oxidation performance under high temperature conditions, while maintaining good processability and manufacturing cost-effectiveness.
Smart Images

Figure 0007671368000003 
Figure 0007671368000004 
Figure 0007671368000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a ferritic stainless steel and a method for producing the same. [Background technology]
[0002] Ferritic stainless steels, which are used in exhaust gas purification catalyst carriers (including electrically heated types) mounted on automobiles and motorcycles, stove combustion tubes, and combustion gas exhaust systems in plants, are required to have high oxidation resistance at high temperatures (high-temperature oxidation resistance).
[0003] Patent Document 1 discloses a high-Al-containing ferritic stainless steel with improved high-temperature oxidation resistance. The high-Al-containing ferritic stainless steel disclosed in Patent Document 1 contains 15-25% Cr and 4.5-6.0% Al. Furthermore, the amounts of Mn and Si added are reduced to reduce the Mn and Si content, and Mo is included as an essential element to improve the high-temperature oxidation resistance of the high-Al-containing ferritic stainless steel. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent No. 3351836 Summary of the Invention [Problem to be solved by the invention]
[0005] However, in the above-mentioned conventional techniques, the addition of Al and Mo in excessive amounts reduces toughness, which may adversely affect manufacturability.
[0006] An object of one aspect of the present invention is to provide a ferritic stainless steel having excellent high-temperature oxidation resistance and toughness. [Means for solving the problem]
[0007] In order to achieve the above object, a ferritic stainless steel according to one embodiment of the present invention contains, by mass%, C: 0.030% or less, Si: 0.01 to 1.5%, Mn: 0.01 to 1.00%, P: 0.050% or less, S: 0.005% or less, Cr: 15.0 to 25.0%, Al: 2.0 to 4.0%, Ni: 1.00% or less, Nb: 0.01 to 0.70%, N: 0.030% or less, B: 0.0003 to 0.01%, REM: 0.01 to 0.20%, with the balance being Fe and unavoidable impurities, and has a dislocation density ρ of 0.91×10 calculated using the Williamson and Hall method. 14 [m -2 ] or more, and when a cross section cut along a plane perpendicular to the rolling direction is observed using a scanning electron microscope at three random locations each having an area of 30 μm × 30 μm, the number of carbides having a Nb concentration of 5 wt% or more and a particle diameter of 0.1 μm or more as measured by energy dispersive X-ray analysis is, on average, 2 to 15.
[0008] A method for producing a ferritic stainless steel according to one embodiment of the present invention contains, by mass%, C: 0.030% or less, Si: 0.01 to 1.5%, Mn: 0.01 to 1.00%, P: 0.050% or less, S: 0.005% or less, Cr: 15.0 to 25.0%, Al: 2.0 to 4.0%, Ni: 1.00% or less, Nb: 0.01 to 0.70%, N: 0.030% or less, B: 0.0003 to 0.01%, REM: 0.01 to 0.20%, and the balance being Fe and unavoidable impurities. The method for producing a ferritic stainless steel according to one embodiment of the present invention includes annealing a hot-rolled steel strip and cooling the annealed steel strip from the annealing temperature to 400° C. for a cooling time of 30 seconds or more, and performing a cooling process using a method according to the Williamson and The dislocation density ρ calculated using the Hall method is 0.91×10 14 [m -2 and a cold rolling step of rolling the steel sheet until the steel sheet has a thickness of at least 100 mm. Effect of the Invention
[0009] According to one aspect of the present invention, a ferritic stainless steel having excellent high-temperature oxidation resistance and toughness can be realized. [Brief description of the drawings]
[0010] [Figure 1] FIG. 2 is a partially enlarged schematic diagram of a cross section of an alumina layer formed by heating an exemplary ferritic stainless steel according to an embodiment at 1050° C. for 50 hours, cut in the thickness direction. [Diagram 2] FIG. 4 is a partially enlarged schematic view of an alumina layer of a comparative example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] [Embodiment] Hereinafter, an embodiment of the present invention will be described in detail. In this specification, the term "stainless steel" refers to a stainless steel material whose specific shape is not limited. Examples of this stainless steel material include steel plates, steel pipes, and bar steel. In this specification, "%", which is the unit of content of each component element, means "mass %" unless otherwise specified. In addition, in this application, "A to B" indicates A or more and B or less.
[0012] (Composition of ferritic stainless steel) First, the essential elements constituting the ferritic stainless steel in this embodiment will be described.
[0013] A ferritic stainless steel according to one embodiment of the present invention has a steel component composition, in mass%, of C: 0.030% or less, Si: 0.01 to 1.5%, Mn: 0.01 to 1.00%, P: 0.050% or less, S: 0.005% or less, Cr: 15.0 to 25.0%, Al: 2.0 to 4.0%, Ni: 1.00% or less, Nb: 0.01 to 0.70%, N: 0.030% or less, B: 0.0003 to 0.01%, and REM: 0.01 to 0.20%.
[0014] When the component composition has a reduced Al content compared to conventional high-Al-containing ferritic stainless steels, a ferritic stainless steel excellent in toughness can be obtained by the ferritic stainless steel according to one embodiment of the present invention having the above component composition.
[0015] Hereinafter, the significance of the content of each element contained in the ferritic stainless steel according to one embodiment of the present invention will be described. Note that the ferritic stainless steel consists of iron (Fe) or a small amount of impurities (inevitable impurities) inevitably mixed therein, except for the following components.
[0016] <C: Carbon> C is an essential element in the ferritic stainless steel according to one embodiment of the present invention. On the other hand, with an increase in the content of C, abnormal oxidation is likely to occur. Further, when C is contained excessively, the toughness of the slab and the hot coil is deteriorated, and it becomes difficult to process into a sheet by hot working. Therefore, in one aspect of the present invention, the upper limit of the content of C is defined as 0.030%. When the content of C is 0.020% or less, the possibility of abnormal oxidation occurrence can be further reduced, and the workability can be improved. In view of the above reasons, the more preferable content of C is 0.002 to 0.015%.
[0017] <Si: Silicon> Si is an element effective for improving oxidation resistance and is an essential element in the ferritic stainless steel according to one embodiment of the present invention. On the other hand, when Si is contained excessively, there is a possibility of reducing toughness and workability. Therefore, in one aspect of the present invention, the content of Si is 0.01 to 1.50%. By setting the content of Si to 0.01 to 1.0%, more preferably 0.01 to 0.50%, the effect as a deoxidizer and the workability are further improved.
[0018] <Mn: Manganese> Mn is an essential element in the ferritic stainless steel according to an embodiment of the present invention. On the other hand, if Mn is contained excessively, the ferrite phase may be destabilized and the high-temperature oxidation resistance may be reduced. Therefore, in one aspect of the present invention, the content of Mn is 0.01 to 1.00%. By setting the content of Mn to 0.01 to 0.80%, more preferably 0.01 to 0.50%, the possibility of the occurrence of corrosion initiation points can be further reduced.
[0019] <P: Phosphorus> P is an essential element in the ferritic stainless steel according to an embodiment of the present invention. On the other hand, if P is contained excessively, the oxidation resistance and the toughness of the hot-rolled sheet may deteriorate. Therefore, in one aspect of the present invention, the content of P is defined to be 0.050% or less. By setting the content of P to 0.04% or less, the deterioration of workability can be further reduced. In view of the above reasons, the more preferable content of P is 0.005 to 0.03%.
[0020] <S: Sulfur> S is an essential element in the ferritic stainless steel according to an embodiment of the present invention. On the other hand, if S is contained excessively, it may have an adverse effect on the formation of the Al2O3 film in the ferritic stainless steel and may deteriorate the oxidation resistance. Therefore, in one aspect of the present invention, the content of S is defined to be 0.005% or less. In view of the above reasons, the more preferable content of S is 0.0001 to 0.002%.
[0021] <Cr: Chromium> Cr is a basic alloying element necessary for improving the high-temperature oxidation characteristics of ferritic stainless steel. By containing Cr in a predetermined amount or more, an oxide film is formed on the surface of the stainless steel, and the oxidation of the stainless steel is suppressed. On the other hand, if excessive Cr is contained, the toughness decreases and the manufacturability deteriorates. Therefore, in one aspect of the present invention, the content of Cr is defined to be 15.0 to 25.0%. By setting the content of Cr to 16.0 to 22.0%, more preferably 17.0 to 20.0%, the oxidation suppression effect and the manufacturability can be further improved.
[0022] <Aluminum> Al is a basic alloying element necessary to improve the high-temperature oxidation resistance of ferritic stainless steel. By containing a predetermined amount or more of Al, an oxide film of Al2O3 is formed on the surface of the stainless steel, and the oxidation of the stainless steel is suppressed. Further, when REM or Y is added, the oxide film becomes dense and the adhesion to the base steel is improved, suppressing the occurrence of abnormal oxidation. On the other hand, when Al is contained in excess, the toughness of the stainless steel deteriorates, and the manufacturability and workability deteriorate. Therefore, in one aspect of the present invention, the content of Al is defined to be 2.0 to 4.0%. By setting the content of Al to 2.5 to 3.7%, more preferably 2.8 to 3.5%, the high-temperature oxidation resistance and manufacturability can be further improved.
[0023] <Nickel> Ni is an element that improves the corrosion resistance of ferritic stainless steel and is an essential element in the ferritic stainless steel according to one embodiment of the present invention. On the other hand, when Ni is contained in excess, the ferrite phase becomes unstable and the material cost increases. Therefore, in one aspect of the present invention, the content of Ni is defined to be 1.00% or less. By setting the content of Ni to 0.50% or less, the destabilization of the ferrite phase due to excessive content and the increase in manufacturing cost can be further suppressed. In view of the above reasons, the more preferable content of Ni is 0.02 to 0.30%.
[0024] <Nitrogen> N is an essential element in the ferritic stainless steel according to one embodiment of the present invention. On the other hand, when contained in excess, it may combine with Al in the steel to form AlN, which may become a starting point for accelerated oxidation. Therefore, in one aspect of the present invention, the content of N is defined to be 0.030% or less. By setting the content of N to 0.025% or less, the possibility of hardening can be further reduced. In view of the above reasons, the more preferable content of N is 0.003 to 0.020%.
[0025] <Nb (niobium), B (boron), REM (rare earth elements)> Nb is an element added to ensure high-temperature strength. Furthermore, Nb has the effect of promoting the formation of an Al2O3 film. Also, it suppresses the recrystallization of stainless steel and widens the grain boundary area by refining the crystal grains. On the other hand, if Nb is contained excessively, the toughness of the hot-rolled sheet may deteriorate.
[0026] B is an element that improves the secondary workability and oxidation resistance of a molded product manufactured using ferritic stainless steel. On the other hand, if B is contained excessively, compounds of B will become inclusions (impurities).
[0027] REM (rare earth metals) refers to lanthanoid series elements (elements with atomic numbers 57 - 71 such as La, Ce, Pr, Nd, Sm). REM is an element that improves high-temperature oxidation resistance. By containing a predetermined amount or more of REM, the Al oxide film is stabilized. Also, the oxidation resistance is improved by improving the adhesion between the base material and the oxide. On the other hand, if REM is contained excessively, surface defects will occur during hot rolling, and the manufacturability will decrease.
[0028] For the above reasons, in one aspect of the present invention, the content of Nb is defined as 0.01 - 0.70%. By setting the content of Nb to 0.05 - 0.50%, more preferably 0.08 - 0.30%, the possibility of deterioration of workability can be further reduced. The upper limit of the content of Nb is more preferably 0.20% or 0.15%. Also, the content of B is defined as 0.0003 - 0.01%. By setting the content of B to 0.0003 - 0.005%, the presence of more inclusions can be reduced and the secondary workability can be improved. Also, the content of REM is defined as 0.01 - 0.20%. The content of REM is preferably 0.02 - 0.15%, and more preferably 0.04 - 0.10%.
[0029] (Other components) The ferritic stainless steel according to one aspect of the present invention may further contain at least one element selected from Zr, V, Cu, Mo, W, Hf, Sn, Ta, Ti, Mg, and Ca as elements other than those described above.
[0030] <Zr: Zirconium> Zr is an element that improves oxidation resistance. On the other hand, excessive addition of Zr may harden the steel and cause a decrease in toughness. Therefore, in one aspect of the present invention, it may contain 0.50% or less of Zr. Considering reduction of hardening and the like, the content of Zr is more preferably 0.01 to 0.40%.
[0031] <V: Vanadium> V is an element that improves workability and toughness of the welded part. On the other hand, excessive addition of V may deteriorate the toughness of the hot-rolled sheet. In one aspect of the present invention, it may contain 0.50% or less of V. Considering reduction of hardening and the like, the content of V is more preferably 0.02 to 0.35%.
[0032] <Cu: Copper> Cu is an element that improves the corrosion resistance of ferritic stainless steel. On the other hand, excessive content of Cu may cause a decrease in oxidation resistance and hot workability. Therefore, in one aspect of the present invention, it may contain 1.0% or less of Cu. Considering material cost and the like, the content of Cu is more preferably 0.01 to 0.85%.
[0033] <Mo: Molybdenum> Mo is an element that improves corrosion resistance. On the other hand, excessive content of Mo hardens, reduces toughness, and increases material cost. Therefore, in one aspect of the present invention, it may contain 2.0% or less of Mo. Considering workability, material cost and the like, the content of Mo is more preferably 0.01 to 1.0%.
[0034] <W: Tungsten> W is an element added to ensure high-temperature strength. On the other hand, excessive W content deteriorates the hot-rolled sheet toughness and increases material costs. Therefore, in one embodiment of the present invention, W may be contained in an amount of 2.0% or less. In consideration of material costs, the W content is more preferably 0.01 to 1.0%.
[0035] <Hf:ハフニウム> Hf is an element that improves oxidation resistance. On the other hand, excessive Hf content reduces the toughness of the hot-rolled sheet and increases the material cost. Therefore, in one embodiment of the present invention, 0.50% or less of Hf may be contained. In consideration of toughness and material cost, the Hf content is more preferably 0.001 to 0.20%.
[0036] <Sn:スズ> Sn (tin) is an element that improves the corrosion resistance of ferritic stainless steel. On the other hand, if the content of Sn is excessive, the workability decreases and the material cost increases. Therefore, in one embodiment of the present invention, the content of Sn may be 0.50% or less. In consideration of the workability, the cost, etc., the content of Sn is more preferably 0.005 to 0.20%.
[0037] <Ta:タンタル> Ta is an element that improves the cleanliness and oxidation resistance of steel. On the other hand, excessive Ta content reduces toughness and increases material costs. Therefore, in one embodiment of the present invention, Ta may be contained in an amount of 0.5% or less. In consideration of toughness and material costs, the Ta content is preferably 0.40% or less. In view of the above reasons, the Ta content is more preferably 0.001 to 0.30%.
[0038] <Ti:チタン> Ti reacts with C and / or N to make the ferritic stainless steel into a ferritic single layer at 900 to 1000°C. On the other hand, excessive Ti content may generate TiO2 in the oxide of Al, which may deteriorate the oxidation life. Therefore, in one embodiment of the present invention, 0.20% or less of Ti may be contained. In consideration of workability, the Ti content is more preferably 0.005 to 0.10%.
[0039] <Mg:マグネシウム> Mg forms Mg oxide together with Al in molten steel and acts as a deoxidizer. On the other hand, excessive Mg content reduces the toughness of the steel and decreases manufacturability. Therefore, in one embodiment of the present invention, 0.015% or less of Mg may be contained. In view of the above reasons, the preferred Mg content is 0.0002 to 0.0080%.
[0040] <Ca:カルシウム> Ca is an element that improves hot workability. On the other hand, if Ca is contained in an excessive amount, the toughness of the steel decreases, and the manufacturability decreases. Therefore, in one embodiment of the present invention, Ca may be contained in an amount of 0.015% or less. In view of the above reasons, the preferred Ca content is 0.0001 to 0.012%.
[0041] The ferritic stainless steel according to this embodiment may satisfy 100×[C] / [Nb]≦35, where [C] is the mass % of C and [Nb] is the mass % of Nb. This allows Nb-based carbides to form during hot rolling or annealing, thereby increasing the amount of accumulated strain during final cold rolling and allowing the desired dislocation density to be obtained.
[0042] (dislocation density) The ferritic stainless steel according to this embodiment has a dislocation density ρ of 0.91×10 calculated by the Williamson and Hall method using X-ray diffraction. 14 [m -2 In this embodiment, the X-ray diffraction is measured from the surface.
[0043] Dislocation density is a value that indicates the amount of dislocations in a crystal, and is the number of coordination lines that penetrate a unit area of a cut surface of a crystal [m -2 ] or the total length of dislocation lines in a unit volume of crystal [m / m -3 The ferritic stainless steel according to this embodiment has a dislocation density ρ of 0.91×10 14 [m -2 By satisfying the above condition, the diffusion of Al and Cr is fast and the alumina layer can be formed quickly, thereby improving the oxidation resistance.
[0044] In this embodiment, the dislocation density ρ [m -2 ] is derived using the Williamson and Hall method. More specifically, for example, it is derived as follows. That is, for a sample that has been subjected to electrolytic polishing, a diffraction intensity curve is measured for each diffraction peak (2θ) of α(110) 52.2°, α(211) 99.3°, and α(229) 123.3° using an X-ray diffractometer using a Co tube as an X-ray source. The diffraction peak (2θ) in the obtained diffraction intensity curve is separated into a peak due to Kα1 ray and a peak due to Kα2 ray. For the separated diffraction peak due to Kα1 ray, the diffraction angle 2θ is specified using the peak top method, and the angle between the intensities at 1 / 2 of the peak intensity is calculated as the half-width. The true half-width β is calculated by subtracting the half-width β of the steel material after cold rolling from the half-width β of the steel material after cold rolling. m and the half-value width β0 of the steel material after final annealing, it can be calculated using the following formula (1).
[0045] β 2 =β m 2 -β0 2 (1) The true full width at half maximum β calculated by the above formula (1) is expressed as the sum of the spread β1 of the full width at half maximum due to the crystallite size D and the spread β2 of the full width at half maximum due to the strain ε, as shown in the following formula (2).
[0046] β = β1 + β2(2) It is known that the spread β1 of the half-width due to the crystallite size (D) is expressed by the following formula (3), and the spread β2 of the half-width due to the strain (ε) is expressed by the following formula (4).
[0047] β1=0.9λ / (Dcosθ) (3) β2=2εtanθ (4) Here, λ in equation (3) is the wavelength of the X-rays.
[0048] By rearranging the above formula (2) using the above formulas (3) and (4), the following formula (5) is obtained.
[0049] βcosθ / λ=(0.9 / D)+(2εsinθ / λ) (5) As shown in the above formula (5), the strain ε can be calculated from the slope of a graph produced by plotting βcosθ / λ against sinθ / λ.
[0050] Then, the dislocation density ρ is calculated by using the calculated strain (ε), the magnitude b (=0.25 nm) of the Burgers vector of the dislocation, and the following equation (6).
[0051] ρ = (14.4 × ε 2 ) / b 2 (3) (Nb carbide) In the ferritic stainless steel according to the present embodiment, when a cross section cut along a plane perpendicular to the rolling direction is observed at three random locations each having an area of 30 μm×30 μm using a scanning electron microscope (SEM), the number of Nb carbides having an Nb concentration of 5 wt% or more and a particle size of 0.1 μm or more measured by EDS analysis is 2 to 15 on average. When the average number is 2 or more, strain is easily accumulated in the structure during cold rolling. Also, when the average number is 15 or less, the toughness of the stainless steel is less likely to decrease. The particle size of the carbide is calculated from the size of the particle in an image captured by a scanning electron microscope. Specifically, the average width between the maximum width and the minimum width in the carbide is taken as the particle size of the carbide.
[0052] (Alumina layer) The ferritic stainless steel according to the present disclosure can be suitably applied to applications requiring oxidation resistance at high temperatures. Therefore, "under use conditions" means under high temperature conditions. The following describes the alumina layer 10 formed when the ferritic stainless steel according to the present disclosure is heated at 1050°C for 50 hours.
[0053] As a result of intensive research, the inventors have found that when Nb, Cr and REM are contained as essential elements in the ferritic stainless steel at concentrations within the appropriate range, the columnar crystallization of the alumina layer formed under the usage conditions is improved. This is believed to be due to the concentration of Nb, Cr and REM at the grain boundaries of the alumina layer. In the alumina layer 10 according to this embodiment, the total concentration of Nb oxides, Cr oxides and REM-based oxides present in the grain boundaries is 3.5 wt% or more. This suppresses the inward diffusion of oxygen, so that the alumina layer 10 has excellent oxidation resistance. That is, the ferritic stainless steel according to this embodiment has excellent oxidation resistance under high temperature conditions.
[0054] The present inventors have also found that the columnar crystallization is improved by including B as an essential element in a concentration within an appropriate range.
[0055] The ferritic stainless steel according to this embodiment contains, by mass%, C: 0.030% or less, Si: 0.01 to 1.5%, Mn: 0.01 to 1.00%, P: 0.050% or less, S: 0.005% or less, Cr: 15.0 to 25.0%, Al: 2.0 to 4.0%, Ni: 1.00% or less, Nb: 0.01 to 0.70%, N: 0.030% or less, B: 0.0003 to 0.01%, and REM: 0.01 to 0.20%.
[0056] The alumina layer 10 formed by heating the ferritic stainless steel containing the above components at 1050° C. for 50 hours has the following characteristics: 2 The total length of grain boundaries included in any one of the regions is 5.5 μm or less.
[0057] 1 is a partially enlarged schematic diagram of a cross section of an alumina layer 10 formed by heating an exemplary ferritic stainless steel according to this embodiment at 1050° C. for 50 hours, cut in the thickness direction. 2 The region may be, for example, a region surrounded by a 1.5 μm square having a center at the center in the thickness direction of the alumina layer 10. 2 The grain boundary length included in the area is 2.25 μm 2 In the example shown in Figure 1, the length of the grain boundary GB is 2.25 μm. 2 The grain boundary length contained in this region is 5.5 μm or less.
[0058] Figure 2 shows the 2.25 μm 2 2 is a partial schematic enlarged view of a comparative alumina layer 20 in which the grain boundary length included in the 2.25 μm region is longer than 5.5 μm. 2The comparative alumina layer 20, which contains grain boundaries having a length longer than 5.5 μm, has a higher ratio of equiaxed crystals than the example shown in FIG.
[0059] Here, the columnar crystals refer to a structure in which elongated crystal grains are arranged in the thickness direction of the alumina layer, and the equiaxed crystals refer to a polycrystalline structure in which the crystal grains constituting the equiaxed crystals are isotropic in shape and orientation.
[0060] As is clear from a comparison of Figures 1 and 2, an alumina layer with a high ratio of columnar crystals (Figure 1) has a shorter grain boundary GB length per any unit area than an alumina layer with a high ratio of equiaxed crystals (Figure 2).
[0061] The alumina layer 10 according to this embodiment is cut in the thickness direction, and the cross section is 2 is 5.5 μm or less. In other words, the alumina layer 10 has a high columnar crystal ratio. Since equiaxed crystals have a higher grain boundary density than columnar crystals, the number of grain boundary diffusion paths for oxygen increases. Therefore, equiaxed crystals have a shorter oxidation life than columnar crystals. Therefore, the ferritic stainless steel according to this embodiment has a high columnar crystal ratio and therefore has excellent oxidation resistance under high temperature conditions.
[0062] (Manufacturing method) First, an example of a manufacturing process for the ferritic stainless steel according to the present embodiment will be described in brief. The manufacturing process for the ferritic stainless steel according to the present embodiment includes a pretreatment process, a hot rolling process, an annealing process, a pickling process, and a cold rolling process.
[0063] In the pretreatment step, first, a melting furnace in a vacuum or argon atmosphere is used to melt steel having a composition adjusted to fall within the range of the present invention, and the steel is cast to produce a slab. Then, a slab piece for hot rolling is cut out from the slab. Then, the slab piece is heated to a temperature range of 1100°C to 1300°C in an air atmosphere. The time for which the slab piece is heated and held is not limited. When the pretreatment step is carried out industrially, the casting may be continuous casting.
[0064] The hot rolling process is a process in which the slab (steel ingot) obtained in the pretreatment process is hot rolled to produce a hot rolled steel strip having a predetermined thickness.
[0065] The annealing process is a process for softening the hot-rolled steel strip obtained in the hot rolling process by heating the steel strip to, for example, 900 to 1050°C. In the annealing process, the steel strip after annealing is cooled from the annealing temperature to 400°C for 30 seconds or more. This allows Nb carbide to precipitate inside the structure (i.e., grain boundaries and inside the grains).
[0066] The pickling step is a step of washing off scale adhering to the surface of the annealed steel strip obtained in the annealing step using a pickling solution such as hydrochloric acid or a mixture of nitric acid and hydrofluoric acid.
[0067] The cold rolling step is a step in which the annealed steel strip from which the scale has been removed in the first pickling step is further rolled to be thinner. The rolling reduction in the cold rolling step is 65% or more, and preferably 75% or more. By setting the rolling reduction in the cold rolling step to 65% or more, the strain in the steel can be increased. More specifically, by setting the rolling reduction in the cold rolling step to 65% or more, the dislocation density ρ derived by the Williamson and Hall method using X-ray diffraction can be increased to 0.91×10 14 [m -2 In other words, the dislocation density ρ calculated by the Williamson and Hall method using X-ray diffraction is 0.91×10 14 [m -2 In order to produce a cold-rolled sheet having a hardness of 100% or more, the rolling ratio in the cold rolling step may be set to 65% or more, and preferably 75% or more.
[0068] The series of steps from the annealing step to the cold rolling step may be performed multiple times. When the series of steps is performed once, the annealing step is referred to as a final annealing step. When the series of steps is performed multiple times, the final annealing step is referred to as a final annealing step, and the other annealing steps are referred to as intermediate annealing steps.
[0069] In the manufacturing method according to the present embodiment, the rolling ratio in the cold rolling process after the final annealing process is 65% or more. In other words, the cold rolling process after the final annealing process is performed so that the dislocation density ρ calculated by the Williamson and Hall method using X-ray diffraction is 0.91×10 14 [m -2 This is a cold rolling process in which the steel is rolled until it reaches a thickness of at least 1 / 2 mm.
[0070] The manufacturing method of the ferritic stainless steel according to the present embodiment is characterized in that it does not include an annealing step after the cold rolling step. That is, the ferritic stainless steel according to the present embodiment is a cold-rolled steel strip after the cold rolling step. Since the ferritic stainless steel is a cold-rolled steel strip, strain remains accumulated in the steel, and the diffusion of Al and Cr is accelerated. Therefore, an alumina layer can be formed early under high temperature conditions, and high high-temperature oxidation resistance can be realized. In addition, since there is no need to perform final annealing after cold rolling, the manufacturing cost can be reduced.
[0071] (summary) The ferritic stainless steel according to the first embodiment of the present disclosure contains, by mass%, C: 0.030% or less, Si: 0.01 to 1.5%, Mn: 0.01 to 1.00%, P: 0.050% or less, S: 0.005% or less, Cr: 15.0 to 25.0%, Al: 2.0 to 4.0%, Ni: 1.00% or less, Nb: 0.01 to 0.70%, N: 0.030% or less, B: 0.0003 to 0.01%, REM: 0.01 to 0.20%, with the balance being Fe and unavoidable impurities, and has a dislocation density ρ of 0.91×10 calculated by the Williamson and Hall method using X-ray diffraction. 14 [m -2 ]That's all.
[0072] According to the above-mentioned configuration, since the content of Al is 4.0% or less, the toughness is excellent. In addition, the dislocation density ρ is 0.91×10 14 [m -2Since the alumina layer can be formed quickly by satisfying the above condition, a ferritic stainless steel having excellent oxidation resistance at high temperatures can be obtained.
[0073] The ferritic stainless steel according to the second aspect of the present disclosure is, in the first aspect, when heated at 1050° C. for 50 hours, an alumina layer mainly composed of alumina is formed, and the alumina layer has an area of 2.25 μm in a cross section obtained by cutting the alumina layer in the thickness direction. 2 The total length of grain boundaries included in any one of the regions may be 5.5 μm or less.
[0074] The ferritic stainless steel according to embodiment 3 of the present disclosure is similar to embodiment 2 above, in that the alumina layer may have a total concentration of Nb oxides, Cr oxides and REM oxides present in the grain boundaries of 3.5 wt% or more.
[0075] The ferritic stainless steel according to aspect 4 of the present disclosure, in any of aspects 1 to 3 above, may further contain, by mass%, one or more of Zr: 0.50% or less, V: 0.50% or less, Cu: 1.0% or less, Mo: 2.0% or less, W: 2.0% or less, Hf: 0.50% or less, Sn: 0.50% or less, Ta: 0.5% or less, Ti: 0.20% or less, Mg: 0.015% or less, and Ca: 0.015% or less.
[0076] The ferritic stainless steel according to aspect 5 of the present disclosure may be any of aspects 1 to 4 above, where [C] is the mass% of C and [Nb] is the mass% of Nb, and satisfies 100×[C] / [Nb]≦35.
[0077] A method for producing a ferritic stainless steel according to a sixth aspect of the present disclosure is a method for producing a ferritic stainless steel containing, by mass%, C: 0.030% or less, Si: 0.01 to 1.5%, Mn: 0.01 to 1.00%, P: 0.050% or less, S: 0.005% or less, Cr: 15.0 to 25.0%, Al: 2.0 to 4.0%, Ni: 1.00% or less, Nb: 0.01 to 0.70%, N: 0.030% or less, B: 0.0003 to 0.01%, REM: 0.01 to 0.20%, and the balance being Fe and unavoidable impurities, the method comprising the steps of: annealing a hot-rolled steel strip; and cooling the steel strip from the annealing temperature to 400° C. for 30 seconds or more after the final annealing step. The dislocation density ρ calculated using the Hall method is 0.91×10 14 [m -2 and a cold rolling step of rolling the steel sheet until the steel sheet has a thickness of at least 100 mm.
[0078] According to the above-mentioned configuration, a ferritic stainless steel having excellent toughness and oxidation resistance at high temperatures can be realized.
[0079] A seventh aspect of the present disclosure relates to a method for producing a ferritic stainless steel according to the sixth aspect, wherein the cold rolling step has a rolling reduction rate of 65% or more.
[0080] A method for producing a ferritic stainless steel according to aspect 8 of the present disclosure may be such that, in aspect 6 or 7 above, the ferritic stainless steel obtained through the cold rolling step has an average number of carbides having a Nb concentration of 5 wt% or more and a particle size of 0.1 μm or more, as measured by energy dispersive X-ray analysis, of 2 to 15, when a cross section cut along a plane perpendicular to the rolling direction is observed using a scanning electron microscope at three random locations each having an area of 30 μm x 30 μm.
[0081] A ninth aspect of the present disclosure relates to a method for producing a ferritic stainless steel in any one of the sixth to eighth aspects, wherein the ferritic stainless steel obtained through the cold rolling step forms an alumina layer when heated at 1050° C. for 50 hours, and the alumina layer has an area of 2.25 μm or less in a cross section obtained by cutting the alumina layer in the thickness direction. 2 The total length of grain boundaries included in any one of the regions may be 5.5 μm or less.
[0082] In the method for producing a ferritic stainless steel according to aspect 10 of the present disclosure, in the above-mentioned aspect 9, the total concentration of Nb oxides, Cr oxides and REM oxides present in the grain boundaries in the alumina layer may be 3.5 wt% or more.
[0083] A method for producing a ferritic stainless steel according to aspect 11 of the present disclosure is any one of aspects 6 to 10 above, wherein the ferritic stainless steel may further contain, by mass%, one or more of Zr: 0.50% or less, V: 0.50% or less, Cu: 1.0% or less, Mo: 2.0% or less, W: 2.0% or less, Hf: 0.50% or less, Sn: 0.50% or less, Ta: 0.5% or less, Ti: 0.20% or less, Mg: 0.015% or less, and Ca: 0.015% or less.
[0084] A method for producing a ferritic stainless steel according to aspect 12 of the present disclosure is any one of aspects 6 to 11 above, wherein the ferritic stainless steel satisfies 100×[C] / [Nb]≦35, where [C] is the mass% of C and [Nb] is the mass% of Nb.
[0085] In the method for producing a ferritic stainless steel according to a thirteenth aspect of the present disclosure, in any one of the sixth to twelfth aspects, the heating temperature in the final annealing step may be 900° C. to 1050° C. This configuration makes it possible to obtain an annealed steel strip suitable for realizing a ferritic stainless steel having excellent toughness and oxidation resistance at high temperatures.
[0086] [Example] In order to evaluate the physical properties of the ferritic stainless steel of the present invention, ferritic stainless steels were produced as example steels and comparative steels using the components shown in Table 1 below. In Table 1, steel types No. 1 to 16 are ferritic stainless steels as examples of the present invention produced within the scope of the present invention. Also in Table 1, steel types No. 17 to 27 are ferritic stainless steels as comparative examples produced under conditions outside the scope of the present invention.
[0087] In producing the steel materials of the steel types shown in Table 1, first, the steels having the components shown in Table 1 were vacuum melted to produce 30 kg slabs. The slabs were heated at 1230°C for 2 hours and then hot rolled to produce hot-rolled sheets with a thickness of 3 mm. The obtained hot-rolled sheets were annealed between 900 and 1050°C to produce hot-rolled annealed sheets. The obtained hot-rolled annealed sheets were cold-rolled and annealed twice, and then finally cold-rolled to produce cold-rolled sheets with a thickness of 50 μm. The cooling time from the annealing temperature to 400°C in the annealing process is shown in Table 2.
[0088] The first two cold rollings were performed at a rolling reduction of 60-85% in both the inventive examples and the comparative examples, and annealing after cold rolling was performed in a temperature range of 900-1050°C. The rolling reduction in the final cold rolling is shown in the "Final rolling reduction" column of Table 2. As shown in Table 2, the rolling reduction in the final cold rolling in the inventive examples is 65% or more. On the other hand, the rolling reduction in the final cold rolling in the comparative examples is less than 65%. The manufacturing method described in this example is an example, and is not intended to limit the manufacturing method. [Table 1]
[0089] Table 1 shows the composition of the components contained in each steel grade in mass %. The remainder other than the components shown in Table 1 is Fe or small amounts of impurities that are inevitably mixed in (unavoidable impurities). The underlines in Table 1 indicate that the range of each component contained in each stainless steel according to the comparative example of the present invention is outside the range of the present invention.
[0090] (Measurement of dislocation density) The following describes the measurement of dislocation density ρ performed on the cold-rolled sheets of the steel types of the present invention examples and the steel types of the comparative examples shown in Table 1. The dislocation density ρ was measured according to the method explained in the section (Dislocation Density) in the embodiment. Table 2 shows the measurement results of dislocation density ρ. All of the steel types No. 1 to No. 16, which are examples of the present invention, have a dislocation density ρ of 0.91×10 14 [m -2 On the other hand, the comparative steels No. 17 to 27 all had a dislocation density ρ of 0.91 × 10 14 [m -2 From these results, it was found that when the reduction ratio in the final cold rolling is 65% or more, the dislocation density ρ is 0.91 × 10 14 [m -2 On the other hand, when the reduction ratio in the final cold rolling is less than 65%, the dislocation density ρ is 0.91×10 14 [m -2 ] or less.
[0091] (Nb carbide) The number of Nb carbides present in the structure was investigated for the cold-rolled sheets of the steel types of the present invention and the steel types of the comparative examples shown in Table 1. The investigation was carried out as follows. First, the cold-rolled sheets were cut on a plane perpendicular to the rolling direction. Next, the cut surfaces were observed at three random locations within an area of 30 μm × 30 μm using a scanning electron microscope, and the average number of carbides with a Nb concentration of 5 wt% or more and a particle size of 0.1 μm or more measured by energy dispersive X-ray analysis was calculated. The calculated average value of Nb carbides is shown in Table 2 as the "average number of Nb carbides." As shown in Table 2, the average number of carbides was in the range of 2 to 15 for all of the steel types No. 1 to 16 of the present invention.
[0092] (Grain boundary length measurement) First, cold-rolled sheets of the steel types of the present invention and comparative steel types shown in Table 1 were heated at 1050°C for 50 hours. After heating, each steel sheet was observed from the cross section using STEM. STEM observation was performed using a Hitachi High-Tech HD-2700 at a voltage of 200V and an observation magnification of 30,000 times. The alumina grain boundary length was measured by randomly selecting a 1.5 μm x 1.5 μm range from the center of the alumina coating, and the total length of the grain boundaries within that range was determined. The measured length was the average value of three randomly selected locations.
[0093] In the judgment of grain boundary length in Table 2, "〇 (good)" is 2.25 μm 2 The grain boundary length is within the range of 5.5 μm or less, and "× (bad)" is 2.25 μm 2 This indicates that the grain boundary length in the range is greater than 5.5 μm.
[0094] (Element concentration in grain boundaries of alumina layer) The concentrations of Nb, Cr and REM elements in the alumina grain boundaries of the examples of the present invention and the comparative examples shown in Table 1 will be described below.
[0095] First, the cold-rolled sheets of the steel types of the present invention and comparative steel types shown in Table 1 were heated at 1050°C for 50 hours. After heating, each steel sheet was observed from the cross section, and the concentration of each element in the grain boundary was measured by STEM-EDX. STEM image observation was performed using a Hitachi High-Tech HD-2700 at a voltage of 200V and an observation magnification of 4 million times, by spot analyzing the center of the grain boundary. EDX (energy dispersive X-ray analysis) was performed using an energy dispersive X-ray analyzer EDAX Octane T Ultra W manufactured by Ametech. The analysis time was 300 seconds.
[0096] Table 2 shows the total concentration of elements Nb, Cr, Ce, La, and Nd, that is, the total concentration of Nb oxides, Cr oxides, and REM oxides in the grain boundaries.
[0097] In the judgment of the concentration of concentrated elements in Table 2, when the total concentration of Nb oxide, Cr oxide and REM oxide in the grain boundary is 3.5wt% or more, it is indicated as "Good (◯)". On the other hand, when it is less than 3.5wt%, it is indicated as "Poor (×)" in Table 2.
[0098] (High-temperature oxidation resistance evaluation test) The following describes the high-temperature oxidation resistance evaluation test carried out on the examples of the present invention and the comparative examples shown in Tables 1 and 2. First, for each steel type shown in Table 1, three test pieces, each 20 mm wide and 25 mm long, were taken from a cold-rolled sheet with a thickness of 50 μm as described in the manufacturing of the steel material. The test pieces were exposed to an air atmosphere at 1,050°C for 50 hours, and the average oxidation weight gain of the three pieces was measured. This high-temperature oxidation resistance evaluation test was carried out in air using an EREMA electric furnace. The results are shown in Table 3 below. In the judgment of high-temperature oxidation resistance in Table 3, "good" indicates an average oxidation gain of 1 mg / cm 2 or less, and "× (defective)" is 1 mg / cm 2 This indicates that it exceeded the
[0099] (Toughness evaluation test) The toughness evaluation test carried out on the present invention examples and comparative examples shown in Table 1 will be described below. First, the test pieces used in this evaluation test were prepared based on the V-notch test pieces of the JIS standard (JIS Z 2242 (2018)). The plate thickness was adjusted by surface cutting the hot-rolled plate with a plate thickness of 3 mm described in the steel material manufacturing section to a plate thickness of 2.5 mm. The test pieces were taken from the steel plate so that the longitudinal direction of the test pieces was parallel to the rolling direction. In addition, the test pieces were notched so that they were perpendicular to the rolling direction.
[0100] This evaluation test was conducted based on the JIS standard (JIS Z 2242 (2018)). This evaluation test was conducted at room temperature (23°C ± 2°C) on five pieces of each steel type to determine the Charpy impact value (absorbed energy). Note that this evaluation test used a Charpy impact tester, Model IC-30B, manufactured by Tokyo Shoki Seizosho Co., Ltd. The results are shown in Table 2 below. In Table 2, "〇 (good)" indicates a Charpy impact value of 20 J / cm 2"× (bad)" indicates a Charpy impact value of 20 J / cm or more. 2 This indicates that the value is less than 0. [Table 2]
[0101] As shown in Table 2, all of the example steels No. 1 to No. 16 satisfied the above criteria for high-temperature oxidation resistance and toughness. The comparative steels No. 17 to No. 27 did not satisfy the above criteria for either or both of high-temperature oxidation resistance and toughness.
[0102] That is, it has been demonstrated that the ferritic stainless steel within the scope of the present invention has excellent high-temperature oxidation resistance and toughness.
[0103] The reason why the comparative steels No. 17 to 27 do not show better results than the inventive steels will be explained below.
[0104] The comparative steel No. 17 met the standard for grain boundary length, but the concentrations of Nb, Cr, and REM in the grain boundaries did not meet the standards due to the low content of B. As a result, it did not show excellent results in terms of high-temperature oxidation resistance.
[0105] In the comparative steel No. 18, the REM content was less than 0.01%, so the concentrations of Nb, Cr, and REM in the grain boundaries did not meet the standards. In addition, the Ti content of the comparative steel No. 18 was more than 0.20%, so the comparative steel was prone to equiaxed crystallization and did not exhibit excellent high-temperature oxidation resistance.
[0106] Comparative steel No. 19 had a Nb content of less than 0.01%, and the concentrations of Nb, Cr and REM in the grain boundaries did not satisfy the standards, so it did not show excellent high-temperature oxidation resistance.
[0107] In the comparative steel No. 20, the Zr content was more than 0.50%, so Zr was easily segregated at the alumina grain boundaries, which promoted equiaxed crystallization, and the steel did not show excellent high-temperature oxidation resistance.
[0108] Comparative steel No. 21, which has a Si content greater than 1.5%, exhibited excellent high-temperature oxidation resistance due to the effects of Si-based oxides such as SiO2. On the other hand, comparative steel No. 21, which has a Si content greater than 1.5%, did not exhibit good toughness.
[0109] In the comparative steel No. 22, the Al content is less than 2.0%, and the oxide film of Al2O3 is not easily formed. This results in a high oxygen partial pressure, which tends to lead to equiaxed crystallization, and the steel did not show good results in terms of high-temperature oxidation resistance.
[0110] Comparative steel No. 23, which has a Ti content higher than 0.20%, is prone to equiaxed crystallization and did not show good results in terms of high-temperature oxidation resistance.
[0111] Comparative steel No. 24 had a Nb content higher than 0.70% and was prone to equiaxed crystallization, and therefore did not show good results in terms of high-temperature oxidation resistance.
[0112] Comparative steel No. 25, which had an Al content higher than 4.0%, did not show good results in terms of toughness.
[0113] Comparative steel No. 26 had a Cr content higher than 25.0%, and Cr was concentrated at the alumina grain boundaries, tending to form equiaxed crystals, and did not show good results in terms of high-temperature oxidation resistance.
[0114] Comparative steel No. 27 had a REM content of more than 0.20%, which resulted in the formation of oxides such as Y2O3 and CeO2, and therefore did not show good results in terms of toughness. [Explanation of symbols]
[0115] 10 Alumina layer
Claims
1. The alloy contains, by mass%, C: 0.030% or less, Si: 0.01 to 1.5%, Mn: 0.01 to 1.00%, P: 0.050% or less, S: 0.005% or less, Cr: 15.0 to 25.0%, Al: 2.0 to 4.0%, Ni: 1.00% or less, Nb: 0.01 to 0.70%, N: 0.030% or less, B: 0.0003 to 0.01%, REM: 0.01 to 0.20%, and the balance being Fe and unavoidable impurities, and has a dislocation density ρ of 0.91×10 calculated using the Williamson and Hall method. 14 [m -2 ] and above, A ferritic stainless steel in which, when a cross section cut along a plane perpendicular to the rolling direction is observed using a scanning electron microscope at three random locations each having an area of 30 μm x 30 μm, the number of carbides having a Nb concentration of 5 wt % or more and a particle diameter of 0.1 μm or more as measured by energy dispersive X-ray analysis is, on average, 2 to 15.
2. When heated at 1050° C. for 50 hours, an alumina layer mainly made of alumina is formed. The alumina layer has a cross section having an area of 2.25 μm when cut in the thickness direction of the alumina layer. 2 2. The ferritic stainless steel according to claim 1, wherein the total length of grain boundaries included in any one of the above regions is 5.5 μm or less.
3. 3. The ferritic stainless steel according to claim 2, wherein the total concentration of Nb oxides, Cr oxides and REM oxides present in the grain boundaries in the alumina layer is 3.5 wt % or more.
4. 4. A ferritic stainless steel according to claim 1, further containing, by mass%, one or more of Zr: 0.50% or less, V: 0.50% or less, Cu: 1.0% or less, Mo: 2.0% or less, W: 2.0% or less, Hf: 0.50% or less, Sn: 0.50% or less, Ta: 0.5% or less, Ti: 0.20% or less, Mg: 0.015% or less, and Ca: 0.015% or less.
5. When [C] is the mass% of C and [Nb] is the mass% of Nb, The ferritic stainless steel according to any one of claims 1 to 3, which satisfies 100 x [C] / [Nb] ≦ 35.
6. A method for producing a ferritic stainless steel comprising, by mass%, C: 0.030% or less, Si: 0.01 to 1.5%, Mn: 0.01 to 1.00%, P: 0.050% or less, S: 0.005% or less, Cr: 15.0 to 25.0%, Al: 2.0 to 4.0%, Ni: 1.00% or less, Nb: 0.01 to 0.70%, N: 0.030% or less, B: 0.0003 to 0.01%, REM: 0.01 to 0.20%, and the balance being Fe and unavoidable impurities, An annealing process in which the hot-rolled steel strip is annealed, and the cooling time from the annealing temperature of the steel strip to 400°C after annealing is 30 seconds or more; After the final annealing process, the dislocation density ρ calculated using the Williamson and Hall method is 0.91 × 10 14 [m -2 and a cold rolling step of rolling the steel until the steel has a thickness of at least 100 mm.
7. The method for producing a ferritic stainless steel according to claim 6, wherein the cold rolling step has a rolling reduction of 65% or more.
8. The method for producing a ferritic stainless steel according to claim 6 or 7, wherein, when a cross section of the ferritic stainless steel obtained through the cold rolling process is observed using a scanning electron microscope at three random locations each having an area of 30 μm x 30 μm, the number of carbides having a Nb concentration of 5 wt% or more and a particle diameter of 0.1 μm or more as measured by energy dispersive X-ray analysis is 2 to 15 on average.
9. The ferritic stainless steel obtained through the cold rolling process forms an alumina layer when heated at 1050° C. for 50 hours, The alumina layer has a cross section having an area of 2.25 μm when cut in the thickness direction of the alumina layer. 2 8. The method for producing a ferritic stainless steel according to claim 6 or 7, wherein the total length of grain boundaries included in any one of the above regions is 5.5 μm or less.
10. 10. The method for producing a ferritic stainless steel according to claim 9, wherein the total concentration of Nb oxides, Cr oxides and REM oxides present in the grain boundaries in the alumina layer is 3.5 wt % or more.
11. The method for producing a ferritic stainless steel according to claim 6 or 7, wherein the ferritic stainless steel further contains, by mass%, one or more of Zr: 0.50% or less, V: 0.50% or less, Cu: 1.0% or less, Mo: 2.0% or less, W: 2.0% or less, Hf: 0.50% or less, Sn: 0.50% or less, Ta: 0.5% or less, Ti: 0.20% or less, Mg: 0.015% or less, and Ca: 0.015% or less.
12. The ferritic stainless steel has the following properties, when [C] is the mass% of C and [Nb] is the mass% of Nb: The method for producing a ferritic stainless steel according to claim 6 or 7, wherein 100×[C] / [Nb]≦35 is satisfied.
Citation Information
Patent Citations
Electric automobile gear steel free of carbide bainite and production method of electric automobile gear steel
CN111471938A
High strength ferritic heat resistant steel
JP2002146484A
Ferritic stainless steel and method for producing the same, and fuel cell member
JP2020066794A
High Al content ferritic stainless steel with excellent high-temperature oxidation resistance
JP3351836B2